East Asia's Changing Urban Landscape : Measuring a Decade of Spatial Growth - World Bank Group (Washington, DC: World Bank, 2015)
Urbanization is transforming the developing world. However, understanding the pace, scale, and form of urbanization has been limited by a lack of consistent data. East Asia’s Changing Urban Landscape aims to address this problem by using satellite imagery and other data to measure urban expansion across the East Asia and Pacific region between 2000 and 2010. Illustrated with maps and charts, it presents trends in urban expansion and population growth in more than 850 urban areas -- by country, urban area, income group, and city size categories. It discusses findings related to increasing urban population densities across the region and quantifies the administrative fragmentation of urban areas that cross local boundaries.